Enhancing tomato plant immune responses through microbial bio-inducers against Pythium irregular root rot - Mohamed S. Attia; Mohamed M. Nofel; Amer M. Abdelaziz; Eslam K. Kandil; Abdulrahman E. Singer; Youssef E. Madkour; Mohammed G. Awad; Muostafa M. Abdelsamad; Abdullah A. Mahmoud; Hassan A. Rudayni; Amr Elkelish; Gharieb S. El-Sayyad (Physiological and Molecular Plant Pathology, 2026)

Establishment of Agrobacterium tumefaciens-mediated transformation of Onobrychis viciifiolia Scop. - Tevon Allan Pitambar; Stacy D. Singer; Ling Chen; Susanne E. Kohalmi; Abdelali Hannoufa (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)
Sainfoin ( Onobrychis viciifolia ) is a forage legume crop with resurgent popularity due to its anti-bloating and anthelmintic properties attributed to its relatively high content of condensed tannins. Although this property of sainfoin is desirable, sainfoin lags behind other popular forage crops in attributes, such as biomass yield, waterlogging tolerance, and stand persistence. Traditional breeding efforts to improve sainfoin have been constrained by its tetraploid genome and obligatory outcrossing nature. To accelerate the development of competitive cultivars using molecular-based approaches, a method for stable genetic transformation was needed. Here we describe a method for Agrobacterium tumefaciens -mediated transformation of sainfoin ‘AAC Mountainview’ cotyledons using A. tumefaciens strain GV3101 that produces an average transformation efficiency of 10%. We used the FB_35S::RUBY binary vector for transformation which harbors the RUBY reporter gene to enable quick and easy identification of transformation events early in the tissue culturing process. This research establishes the foundation for future advances in sainfoin through molecular-based improvement.

Elucidating putative novel functions of the AINTEGUMENTA-LIKE 7 transcription factor in clubroot resistance in Arabidopsis - Kethmi Nirmani Jayawardhane; Tharangani K. Somarathna; Victor P. Manoli; Sheau-Fang Hwang; Stephen E. Strelkov; Stacy D. Singer; Guanqun Chen (Plant Molecular Biology, 2026)

Habitat use differences mediate population threat exposure in white sturgeon - Jonathan A. Walter; Gabriel P. Singer; Daniel C. Reuman; Scott F. Colborne; Lawrence W. Sheppard; Daniel R. O’Donnell; Nat Coombs; Erin E. Tracy; Myfanwy Johnston; Emily A. Miller; Anna E. Steel; John T. Kelly; et al. (Environmental Biology of Fishes, 2026)

Plants Anticipating Help: A New Hypothesis in Plant Defence Theory - Michael S. Singer; Tamara M. Kancoglu; Hartmut A. Doerwaldt; Alesandra G. Fairchild; Isabelle E. Harper; Harmony S. Lemire; Caitlin McNamara; Isaac McPherson; Mariema Tall (Ecology Letters, 2026)
Plants can ‘cry for help’ in response to herbivory as well as anticipate herbivory by detecting specific environmental cues before damage occurs. But can plants ‘anticipate help?’ Building on the optimal defence and information transfer models of induced plant defence, we argue they can. We find literature support for key assumptions of the ‘anticipating help’ hypothesis, which proposes plants can (1) detect cues that signal reliable protection from enemies of herbivores (bodyguards), and (2) downregulate direct anti‐herbivore resistance when bodyguards compensate. In an original a priori test of the assumptions of cue detection and downregulation of direct resistance, we use a meta‐analysis of sequential herbivory experiments. We found that plants express induced susceptibility (dampened direct resistance) towards leaf‐chewing herbivores only after induction by myrmecophilous sap‐feeding herbivores, a putative cue for reliable ant‐mediated protection against chewing herbivores. More generally, we expect ‘anticipating help’ behaviour in plants when local environmental cues predict reliable anti‐herbivore protection from bodyguards that compensate for dampened direct resistance at a reduced fitness cost. The ‘anticipating help’ hypothesis can explain several enigmatic issues, such as induced susceptibility, associational resistance of plants, and how indirect resistance may benefit plant fitness under a wider range of conditions than previously recognised.

Long-term common trends in epifauna communities and associated demersal fish assemblages mediated by environmental and human stressors in the south-eastern North Sea - Anja Singer; Ingrid Kröncke; Kim E. Ludwig; Hermann Neumann; Anne F. Sell (Estuarine, Coastal and Shelf Science, 2025)

Mechanisms governing the transport of nanoparticles and microplastics in porous media: A review - Mohamed N. Singer; Batoul Mohsen; Vasileios E. Katzourakis; Maryam R. Al Shehhi; Constantinos V. Chrysikopoulos (Journal of Environmental Chemical Engineering, 2025)

Thermally driven ultrapure water production for water electrolysis – A techno-economic analysis of membrane distillation - R. Schwantes; Y. Morales; E. Pomp; J. Singer; K. Chavan; F. Saravia (Desalination, 2025)

The applicability of regional red list assessments for soil invertebrates: first assessment of five native earthworm species in Canada - Helen R. P. Phillips; George G. Brown; Sam W. James; Jérôme Mathieu; John Warren Reynolds; Maheshi E. Dharmasiri; Claire L. Singer; Maria J. I. Briones; Heather C. Proctor; Erin K. Cameron (Biodiversity and Conservation, 2025)
Earthworms (Annelida: Clitellata: Crassiclitellata) are prominent members of the soil community, important to many ecosystem functions. Despite this, and like many other soil invertebrates, they are rarely considered in conservation assessments, including the International Union for Conservation of Nature (IUCN) Red List assessments used to assess species’ extinction risk. To investigate the applicability of the IUCN Regional Red Listing protocol to soil invertebrates, we assessed the conservation status of five earthworm species native to Canada using this protocol and all available occurrence records. In Canada, no earthworm species have yet been assessed by the Committee on the Status of Endangered Wildlife in Canada (COSEWIC). Due to the lack of data on population sizes and their trends, all five species were assessed using their Extent of Occurrence (EOO) (Criterion B). One species was assessed as Vulnerable ( Arctiostrotus vancouverensis) , two were assessed in non-threatened categories ( A. perrieri and Sparganophilus tamesis ), and two were assessed as Data Deficient ( A. fontinalis and Toutellus oregonensis ). For the majority, the main threats identified were the continuing loss of potential habitat due to land conversion and resource exploitation, as well as the effects of climate change. Increasing the amount of data, including but not limited to distribution and habitat preferences, would make the assessment process easier and status decisions better supported. By undertaking regional assessments for five native earthworm species in Canada, we show that Regional Red List assessments are feasible for soil invertebrates.

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

Clinical and Laboratory Features Predict Phenoconversion from Sporadic Adult-onset Ataxia to Multiple System Atrophy - Tina Liu; Monica Johnson; Negin Badihian; William S. Harmsen; Jay Mandrekar; Lauren M. Jackson; Eduardo E. Benarroch; Paola Sandroni; Phillip A. Low; Wolfgang Singer; Elizabeth A. Coon (The Cerebellum, 2024)

New perspectives on ice forcing in continental arc magma plumbing systems - Brad S. Singer; Pablo Moreno-Yaeger; Meredith Townsend; Christian Huber; Joshua Cuzzone; Benjamin R. Edwards; Matias Romero; Yasmeen Orellana-Salazar; Shaun A. Marcott; Rachel E. Breunig; Ken L. Ferrier; Kathryn Scholz; et al. (Journal of Volcanology and Geothermal Research, 2024)

Urinary metabolite concentrations of phthalate and plasticizers in infancy and childhood in the UNC baby connectome project - Jake E. Thistle; Chih-Wei Liu; Julia E. Rager; Alison B. Singer; Dazhe Chen; Cherrel K. Manley; Joseph Piven; John H. Gilmore; Alexander P. Keil; Anne P. Starling; Hongtu Zhu; Weili Lin; et al. (Environmental Research, 2024)

A Bayesian age from dispersed plagioclase and zircon dates in the Los Chocoyos ash, Central America - Alec Baudry; Brad S. Singer; Brian Jicha; Christine E. Jilly-Rehak; Jorge A. Vazquez; C. Brenhin Keller (Earth and Planetary Science Letters, 2024)

Melt inclusions in zircon: a window to understanding the structure and evolution of the magmatic system beneath the Laguna del Maule volcanic field - Kei Shimizu; Tyler B. Blum; Chloe E. Bonamici; John H. Fournelle; Christine E. Jilly-Rehak; Noriko T. Kita; Kouki Kitajima; Jacob D. Klug; Will O. Nachlas; Brad S. Singer; Michael J. Spicuzza; Alexander V. Sobolev; et al. (Contributions to Mineralogy and Petrology, 2024)

Looking for non-hermaphrodite cacti: multidisciplinary studies in Gymnocalycium bruchii endemic to central Argentina - Natalia E. Delbón; Nayla L. Aliscioni; Marina Lorenzati; Sergio García; Rodrigo B. Singer; Diego E. Gurvich (Plant Reproduction, 2024)

Paleomagnetism and age of the Leucite Hills Volcanic complex, Wyoming: Implications for eruptive history, landscape evolution, and the geomagnetic instability timescale (GITS) - J.T. Welsh; J.M. Feinberg; E. Schneider; J.M. Pares; B.R. Jicha; B.S. Singer; A.R. Carroll (Journal of Volcanology and Geothermal Research, 2023)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Measuring travel problems: Testing a novel survey tool in a natural experiment - Matan E. Singer; Karel Martens (Transportation Research Part D: Transport and Environment, 2023)

Correction to Migrating Ducks and Submersed Aquatic Vegetation Respond Positively After Invasive Common Carp (Cyprinus carpio) Exclusion from a Freshwater Coastal Marsh - Lauren E. Bortolotti; Robert B. Emery; Paige D. Kowal; Llwellyn M. Armstrong; Vanessa B. Harriman; Howard V. Singer; Michael J. Anteau; Frank B. Baldwin; Cameron Meuckon; Dale A. Wrubleski (Wetlands, 2023)

Pulmonary bleeding in racehorses: a gross and histological comparison of exercise-induced pulmonary haemorrhage and exercise associated fatal pulmonary haemorrhage - G. Rocchigiani; R. Verin; F.A. Uzal; E.S. Singer; P. Pregel; L. Ressel; E. Ricci (Journal of Comparative Pathology, 2023)

Migrating Ducks and Submersed Aquatic Vegetation Respond Positively After Invasive Common Carp (Cyprinus carpio) Exclusion from a Freshwater Coastal Marsh - Lauren E. Bortolotti; Robert B. Emery; Paige D. Kowal; Llwellyn M. Armstrong; Vanessa B. Harriman; Howard V. Singer; Michael J. Anteau; Frank B. Baldwin; Cameron Meuckon; Dale A. Wrubleski (Wetlands, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Local groundwater decline exacerbates response of dryland riparian woodlands to climatic drought - Jared Williams; John C. Stella; Steven L. Voelker; Adam M. Lambert; Lissa M. Pelletier; John E. Drake; Jonathan M. Friedman; Dar A. Roberts; Michael Bliss Singer (Global Change Biology, 2022)
Dryland riparian woodlands are considered to be locally buffered from droughts by shallow and stable groundwater levels. However, climate change is causing more frequent and severe drought events, accompanied by warmer temperatures, collectively threatening the persistence of these groundwater dependent ecosystems through a combination of increasing evaporative demand and decreasing groundwater supply. We conducted a dendro‐isotopic analysis of radial growth and seasonal (semi‐annual) carbon isotope discrimination (Δ 13 C) to investigate the response of riparian cottonwood stands to the unprecedented California‐wide drought from 2012 to 2019, along the largest remaining free‐flowing river in Southern California. Our goals were to identify principal drivers and indicators of drought stress for dryland riparian woodlands, determine their thresholds of tolerance to hydroclimatic stressors, and ultimately assess their vulnerability to climate change. Riparian trees were highly responsive to drought conditions along the river, exhibiting suppressed growth and strong stomatal closure (inferred from reduced Δ 13 C) during peak drought years. However, patterns of radial growth and Δ 13 C were quite variable among sites that differed in climatic conditions and rate of groundwater decline. We show that the rate of groundwater decline, as opposed to climate factors, was the primary driver of site differences in drought stress, and trees showed greater sensitivity to temperature at sites subjected to faster groundwater decline. Across sites, higher correlation between radial growth and Δ 13 C for individual trees, and higher inter‐correlation of Δ 13 C among trees were indicative of greater drought stress. Trees showed a threshold of tolerance to groundwater decline at 0.5 m year −1 beyond which drought stress became increasingly evident and severe. For sites that exceeded this threshold, peak physiological stress occurred when total groundwater recession exceeded ~3 m. These findings indicate that drought‐induced groundwater decline associated with more extreme droughts is a primary threat to dryland riparian woodlands and increases their susceptibility to projected warmer temperatures.

The Role of the Cerebellum in Repetitive Behavior Across Species: Childhood Stereotypies and Deer Mice - Shannon L. Dean; Laura Tochen; Farhan Augustine; Syed F. Ali; Deana Crocetti; Shreenath Rajendran; Mary E. Blue; E. Mark Mahone; Stewart H. Mostofsky; Harvey S. Singer (The Cerebellum, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Correction to: Spatio-temporal distribution of Green Sturgeon (Acipenser medirostris) and White Sturgeon (A. transmontanus) in the San Francisco Estuary and Sacramento River, California - Emily A. Miller; Gabriel P. Singer; Matthew L. Peterson; Eric D. Chapman; Myfanwy E. Johnston; Michael J. Thomas; Ryan D. Battleson; Marty Gingras; A. Peter Klimley (Environmental Biology of Fishes, 2020)

Spatio-temporal distribution of Green Sturgeon (Acipenser medirostris) and White Sturgeon (A. transmontanus) in the San Francisco Estuary and Sacramento River, California - Emily A. Miller; Gabriel P. Singer; Matthew L. Peterson; Eric D. Chapman; Myfanwy E. Johnston; Michael J. Thomas; Ryan D. Battleson; Marty Gingras; A. Peter Klimley (Environmental Biology of Fishes, 2020)

Dispersal limitations and historical factors determine the biogeography of specialized terrestrial protists - David Singer; Edward A. D. Mitchell; Richard J. Payne; Quentin Blandenier; Clément Duckert; Leonardo D. Fernández; Bertrand Fournier; Cristián E. Hernández; Gustaf Granath; Håkan Rydin; Luca Bragazza; Natalia G. Koronatova; et al. (Molecular Ecology, 2019)
Recent studies show that soil eukaryotic diversity is immense and dominated by micro‐organisms. However, it is unclear to what extent the processes that shape the distribution of diversity in plants and animals also apply to micro‐organisms. Major diversification events in multicellular organisms have often been attributed to long‐term climatic and geological processes, but the impact of such processes on protist diversity has received much less attention as their distribution has often been believed to be largely cosmopolitan. Here, we quantified phylogeographical patterns in Hyalosphenia papilio , a large testate amoeba restricted to Holarctic Sphagnum ‐dominated peatlands, to test if the current distribution of its genetic diversity can be explained by historical factors or by the current distribution of suitable habitats. Phylogenetic diversity was higher in Western North America, corresponding to the inferred geographical origin of the H. papilio complex, and was lower in Eurasia despite extensive suitable habitats. These results suggest that patterns of phylogenetic diversity and distribution can be explained by the history of Holarctic Sphagnum peatland range expansions and contractions in response to Quaternary glaciations that promoted cladogenetic range evolution, rather than the contemporary distribution of suitable habitats. Species distributions were positively correlated with climatic niche breadth, suggesting that climatic tolerance is key to dispersal ability in H. papilio . This implies that, at least for large and specialized terrestrial micro‐organisms, propagule dispersal is slow enough that historical processes may contribute to their diversification and phylogeographical patterns and may partly explain their very high overall diversity.

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Spatiotemporal occurrence of green sturgeon at dredging and placement sites in the San Francisco estuary - Eric D. Chapman; Emily A. Miller; Gabriel P. Singer; Alex R. Hearn; Michael J. Thomas; William N. Brostoff; Peter E. LaCivita; A. Peter Klimley (Environmental Biology of Fishes, 2019)

Differences in Aggressive Behaviors between Two Ant Species Determine the Ecological Consequences of a Facultative Food-for-Protection Mutualism - Robert E. Clark; Michael S. Singer (Journal of Insect Behavior, 2018)

Keystone mutualism strengthens top–down effects by recruiting large-bodied ants - Robert E. Clark; Michael S. Singer (Oecologia, 2018)

A prospective observational study of problematic oral cannabinoid use - Mark A. Ware; Marc O. Martel; Roman Jovey; Mary E. Lynch; Joel Singer (Psychopharmacology, 2018)

Brain-specific HIV Nef identified in multiple patients with neurological disease - Susanna L. Lamers; Gary B. Fogel; Enoch S. Liu; Andrew E. Barbier; Christopher W. Rodriguez; Elyse J. Singer; David J. Nolan; Rebecca Rose; Michael S. McGrath (Journal of NeuroVirology, 2018)

Multiple interaction types determine the impact of ant predation of caterpillars in a forest community - Robert E. Clark; Timothy E. Farkas; Isaac Lichter‐Marck; Emily R. Johnson; Michael S. Singer (Ecology, 2016)
Direct and indirect effects of predators are highly variable in complex communities, and understanding the sources of this variation is a research priority in community ecology. Recent evidence indicates that herbivore community structure is a primary determinant of predation strength and its cascading impacts on plants. In this study, we use variation in herbivore community structure among plant species to experimentally test two hypotheses in a temperate forest food web. First, variation in the strength of predator effects, such as ant predation of caterpillars, is predicted to be density dependent, exhibiting stronger effects when prey abundance is high (density‐dependent predation hypothesis). Second, mutualistic interactions between ants and sap‐feeding herbivores are expected to increase the abundance of predatory ants, strengthening predation effects on herbivores with cascading effects on host plants (keystone mutualism hypothesis). Using a large‐scale predator exclusion experiment across eight dominant tree species, we tracked changes in insect density on 862 plants across two years, recording 2,322 ants, 1,062 sap‐feeders, 5,322 caterpillars, and quantifying herbivory on 199, 338 leaves. In this experiment, density‐dependent predation did not explain variation in the direct or indirect effects of ants on caterpillars and herbivory. In partial support of the keystone mutualism hypothesis, sap‐feeders strengthened top‐down effects of ants on caterpillars under some conditions. However, stronger ant predation of caterpillars did not lead to measurable trophic cascades on trees occupied by sap‐feeders. Instead, the presence of sap‐feeders was associated with increased per capita feeding damage by caterpillars, and this bottom‐up effect attenuated the indirect effects of ants on host plants. These findings demonstrate that examining the multi‐trophic impacts of mutualisms and predation in the context of the broader community can reveal patterns otherwise masked by compensatory interactions.

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Semiautomated quantitative image analysis of glomerular immunohistochemistry markers desmin, vimentin, podocin, synaptopodin and WT-1 in acute and chronic rat kidney disease models - J. Funk; V. Ott; A. Herrmann; W. Rapp; S. Raab; W. Riboulet; A. Vandjour; E. Hainaut; A. Benardeau; T. Singer; B. Jacobsen (Histochemistry and Cell Biology, 2016)

Movements of steelhead (Oncorhynchus mykiss) smolts migrating through the San Francisco Bay Estuary - Eric D Chapman; Alex R Hearn; Gabriel P Singer; William N Brostoff; Peter E LaCivita; A. Peter Klimley (Environmental Biology of Fishes, 2015)

Movements of out-migrating late-fall run Chinook salmon (Oncorhynchus tshawytscha) smolts through the San Francisco Bay Estuary - Alex R. Hearn; Eric D. Chapman; Gabriel P. Singer; William N. Brostoff; Peter E. LaCivita; A. Peter Klimley (Environmental Biology of Fishes, 2014)

Predictors of CNS injury as measured by proton magnetic resonance spectroscopy in the setting of chronic HIV infection and CART - J. Harezlak; R. Cohen; A. Gongvatana; M. Taylor; S. Buchthal; G. Schifitto; J. Zhong; E. S. Daar; J. R. Alger; M. Brown; E. J. Singer; T. B. Campbell; et al. (Journal of NeuroVirology, 2014)

Can caterpillar density or host-plant quality explain host-plant-related parasitism of a generalist forest caterpillar assemblage? - Timothy E. Farkas; Michael S. Singer (Oecologia, 2013)

A Design Space Verification Protocol for a Small Molecule Drug Substance - Timothy J. N. Watson; Holly Bonsignore; Eileen A. Callaghan-Manning; Stephen T. Colgan; Paul Fitzsimons; Thomas P. Garcia; John G. Groskoph; Michael P. Lynch; Roger Nosal; Megan E. McMahon; Robert A. Singer; Nicholas M. Thomson; et al. (Journal of Pharmaceutical Innovation, 2013)

Growth, survival, and tag retention of steelhead trout (Oncorhynchus mykiss) and its application to survival estimates - P. T. Sandstrom; A. J. Ammann; C. Michel; G. Singer; E. D. Chapman; S. Lindley; R. B. MacFarlane; A. P. Klimley (Environmental Biology of Fishes, 2013)

Interannual variation of reach specific migratory success for Sacramento River hatchery yearling late-fall run Chinook salmon (Oncorhynchus tshawytscha) and steelhead trout (Oncorhynchus mykiss) - Gabriel P. Singer; Alex R. Hearn; Eric D. Chapman; Matthew L. Peterson; Peter E. LaCivita; William N. Brostoff; Allison Bremner; A. P. Klimley (Environmental Biology of Fishes, 2013)

The effects of environmental factors on the migratory movement patterns of Sacramento River yearling late-fall run Chinook salmon (Oncorhynchus tshawytscha) - Cyril J. Michel; Arnold J. Ammann; Eric D. Chapman; Philip T. Sandstrom; Heidi E. Fish; Michael J. Thomas; Gabriel P. Singer; Steven T. Lindley; A. Peter Klimley; R. Bruce MacFarlane (Environmental Biology of Fishes, 2013)

How to understand species’ niches and range dynamics: a demographic research agenda for biogeography - Frank M. Schurr; Jörn Pagel; Juliano Sarmento Cabral; Jürgen Groeneveld; Olga Bykova; Robert B. O’Hara; Florian Hartig; W. Daniel Kissling; H. Peter Linder; Guy F. Midgley; Boris Schröder; Alexander Singer; et al. (Journal of Biogeography, 2012)
Range dynamics causes mismatches between a species’ geographical distribution and the set of suitable environments in which population growth is positive (the Hutchinsonian niche). This is because source–sink population dynamics cause species to occupy unsuitable environments, and because environmental change creates non‐equilibrium situations in which species may be absent from suitable environments (due to migration limitation) or present in unsuitable environments that were previously suitable (due to time‐delayed extinction). Because correlative species distribution models do not account for these processes, they are likely to produce biased niche estimates and biased forecasts of future range dynamics. Recently developed dynamic range models (DRMs) overcome this problem: they statistically estimate both range dynamics and the underlying environmental response of demographic rates from species distribution data. This process‐based statistical approach qualitatively advances biogeographical analyses. Yet, the application of DRMs to a broad range of species and study systems requires substantial research efforts in statistical modelling, empirical data collection and ecological theory. Here we review current and potential contributions of these fields to a demographic understanding of niches and range dynamics. Our review serves to formulate a demographic research agenda that entails: (1) advances in incorporating process‐based models of demographic responses and range dynamics into a statistical framework, (2) systematic collection of data on temporal changes in distribution and abundance and on the response of demographic rates to environmental variation, and (3) improved theoretical understanding of the scaling of demographic rates and the dynamics of spatially coupled populations. This demographic research agenda is challenging but necessary for improved comprehension and quantification of niches and range dynamics. It also forms the basis for understanding how niches and range dynamics are shaped by evolutionary dynamics and biotic interactions. Ultimately, the demographic research agenda should lead to deeper integration of biogeography with empirical and theoretical ecology.

Towards novel approaches to modelling biotic interactions in multispecies assemblages at large spatial extents - W. D. Kissling; Carsten F. Dormann; Jürgen Groeneveld; Thomas Hickler; Ingolf Kühn; Greg J. McInerny; José M. Montoya; Christine Römermann; Katja Schiffers; Frank M. Schurr; Alexander Singer; Jens‐Christian Svenning; et al. (Journal of Biogeography, 2012)
Aim Biotic interactions – within guilds or across trophic levels – have widely been ignored in species distribution models (SDMs). This synthesis outlines the development of ‘species interaction distribution models’ (SIDMs), which aim to incorporate multispecies interactions at large spatial extents using interaction matrices. Location Local to global. Methods We review recent approaches for extending classical SDMs to incorporate biotic interactions, and identify some methodological and conceptual limitations. To illustrate possible directions for conceptual advancement we explore three principal ways of modelling multispecies interactions using interaction matrices: simple qualitative linkages between species, quantitative interaction coefficients reflecting interaction strengths, and interactions mediated by interaction currencies. We explain methodological advancements for static interaction data and multispecies time series, and outline methods to reduce complexity when modelling multispecies interactions. Results Classical SDMs ignore biotic interactions and recent SDM extensions only include the unidirectional influence of one or a few species. However, novel methods using error matrices in multivariate regression models allow interactions between multiple species to be modelled explicitly with spatial co‐occurrence data. If time series are available, multivariate versions of population dynamic models can be applied that account for the effects and relative importance of species interactions and environmental drivers. These methods need to be extended by incorporating the non‐stationarity in interaction coefficients across space and time, and are challenged by the limited empirical knowledge on spatio‐temporal variation in the existence and strength of species interactions. Model complexity may be reduced by: (1) using prior ecological knowledge to set a subset of interaction coefficients to zero, (2) modelling guilds and functional groups rather than individual species, and (3) modelling interaction currencies and species’ effect and response traits. Main conclusions There is great potential for developing novel approaches that incorporate multispecies interactions into the projection of species distributions and community structure at large spatial extents. Progress can be made by: (1) developing statistical models with interaction matrices for multispecies co‐occurrence datasets across large‐scale environmental gradients, (2) testing the potential and limitations of methods for complexity reduction, and (3) sampling and monitoring comprehensive spatio‐temporal data on biotic interactions in multispecies communities.

Erratum to: Restoring Ecological Integrity in Highly Regulated Rivers: The Role of Baseline Data and Analytical References - Peter W. Downs; Maia S. Singer; Bruce K. Orr; Zooey E. Diggory; Tamara C. Church; John C. Stella (Environmental Management, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Restoring Ecological Integrity in Highly Regulated Rivers: The Role of Baseline Data and Analytical References - Peter W. Downs; Maia S. Singer; Bruce K. Orr; Zooey E. Diggory; Tamara C. Church (Environmental Management, 2011)

Genetic resistance to diet-induced obesity in chromosome substitution strains of mice - Lindsay C. Burrage; Annie E. Baskin-Hill; David S. Sinasac; Jonathan B. Singer; Colleen M. Croniger; Andrew Kirby; E. J. Kulbokas; Mark J. Daly; Eric S. Lander; Karl W. Broman; Joseph H. Nadeau (Mammalian Genome, 2010)

Cliniconeuropathologic correlates of human immunodeficiency virus in the era of antiretroviral therapy - I Everall; F Vaida; N Khanlou; D Lazzaretto; C Achim; S Letendre; D Moore; R Ellis; M Cherner; B Gelman; S Morgello; E Singer; et al. (Journal of NeuroVirology, 2009)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Characterizing the regulation of the Pu promoter in Acinetobacter baylyi ADP1 - Wei E. Huang; Andrew C. Singer; Andrew J. Spiers; Gail M. Preston; Andrew S. Whiteley (Environmental Microbiology, 2008)
Summary Effective gene trapping and screening requires sensory and regulatory compatibility of both host and exogenous systems. The naturally competent bacterium Acinetobacter baylyi ADP1 is able to efficiently take up and integrate exogenous DNA into the chromosome, making it an attractive host system for a wide range of metagenomic applications. To test the ability of A. baylyi ADP1 to express the XylR‐regulated Pu promoter from Pseudomonas putida mt‐2, we have constructed and examined an A. baylyi ADP1 strain, ADPWH‐ Pu‐lux‐xylR . The Pu promoter in ADPWH‐ Pu‐lux‐xylR was specifically induced by toluene, m ‐, p ‐ and o‐ xylene. The substrate‐induced Pu promoter was highly dependent on the growth medium: it was repressed in rich media until stationary phase, but was immediately induced in minimal medium with glucose as the sole carbon source (MMG). However, the Pu promoter was repressed in MMG when it was supplemented with 5 g l −1 yeast extract. Further investigation showed that the Pu promoter in MMG was repressed by 0.5 g l −1 aspartic acid or asparagine, but not repressed by glutamine. Changing the carbon/nitrogen ratios by addition of ammonia did not significantly affect the Pu promoter activity but addition of nitrate did. These results show that A. baylyi ADP1 reproduced characteristics of the XylR‐regulated Pu promoter observed in its original host. It demonstrates that A. baylyi could provide an excellent genetic host for a wide range of functional metagenomic applications.

Probability distributions for carbon emissions and atmospheric response - Clifford E. Singer; T. S. Gopi Rethinaraj; Samuel Addy; David Durham; Murat Isik; Madhu Khanna; Brandon Kuehl; Jianding Luo; Wilma Quimio; Kothavari Rajendran; Donna Ramirez; Ji Qiang; et al. (Climatic Change, 2008)

The laminin α-1 chain derived peptide, AG73, increases fibronectin levels in breast and melanoma cancer cells - Jean A. Engbring; Rydhwana Hossain; Sherilyn J. VanOsdol; Benjamin Kaplan-Singer; Michael Wu; Suguru Hibino; Jennifer E. Koblinski (Clinical & Experimental Metastasis, 2008)

Nest demographics and foraging behavior of Apterostigma collare Emery (Hymenoptera, Formicidae) provide evidence of colony independence - T. L. Pitts-Singer; K. E. Espelie (Insectes Sociaux, 2007)

Pollination by Sexual Mimicry in Mormolyca ringens: A Floral Chemistry that Remarkably Matches the Pheromones of Virgin Queens of Scaptotrigona sp. - Adriana Flach; Anita J. Marsaioli; Rodrigo B. Singer; Maria Do Carmo E. Amaral; Cristiano Menezes; Warwick Estevam Kerr; Luciane G. Batista-Pereira; Arlene G. Corrêa (Journal of Chemical Ecology, 2006)

Chromosomally located gene fusions constructed in Acinetobacter sp. ADP1 for the detection of salicylate - Wei E. Huang; Hui Wang; Hongjun Zheng; Linfeng Huang; Andrew C. Singer; Ian Thompson; Andrew S. Whiteley (Environmental Microbiology, 2005)
Summary Acinetobacter sp. ADP1 is a common soil‐associated bacterium with high natural competency, allowing it to efficiently integrate foreign DNA fragments into its chromosome. This property was exploited to engineer salicylate‐inducible luxCDABE and green fluorescent protein (GFP) variants of Acinetobacter sp. ADP1. Specifically, Acinetobacter sp. ADPWH _lux displayed the higher sensitivity when comparing the two variants (minimum detection c . 0.5–1 µM salicylate) and a faster turnover of the lux marker gene, making it suitable for whole‐cell luminescence assays of salicylate concentration. In contrast, the longer maturation and turnover times of the GFP protein make the Acinetobacter sp. ADPWH _gfp variant more suited to applications involving whole‐cell imaging of the presence of salicylate. The sensitivity of the luxCDABE variant was demonstrated by assaying salicylate production in naphthalene‐degrading cultures. Assays using ADPWH _lux specifically mapped the kinetics of salicylate production from naphthalene and were similar to that observed by high‐performance liquid chromatography (HPLC) data. However, ADPWH _lux exhibited the higher sensitivity, when compared with HPLC, for detecting salicylate production during the first 24 h of naphthalene metabolism. These data demonstrate that the engineered Acinetobacter variants have significant potential for salicylate detection strategies in laboratory and field studies, especially in scenarios where genetic stability of the construct is required for in situ monitoring.

The Chemistry of Pollination in Selected Brazilian Maxillariinae Orchids: Floral Rewards and Fragrance - Adriana Flach; Règine Carole Dondon; Rodrigo B. Singer; Samantha Koehler; Maria do Carmo E. Amaral; Anita J. Marsaioli (Journal of Chemical Ecology, 2004)

Analysis of imprinting in mice with uniparental duplication of proximal chromosomes 7 and 15 by use of a custom oligonucleotide microarray - Victoria L. Buettner; Jeffrey A. Longmate; Michael E. Barish; Jeffrey R. Mann; Judith Singer-Sam (Mammalian Genome, 2004)

Acquired and Partially De Novo Synthesized Pyrrolizidine Alkaloids in Two Polyphagous Arctiids and the Alkaloid Profiles of Their Larval Food-Plants - T. Hartmann; C. Theuring; T. Beuerle; L. Ernst; M. S. Singer; E. A. Bernays (Journal of Chemical Ecology, 2004)

Trenching Behavior by Caterpillars of the Euphorbia Specialist, Pygarctia roseicapitis: A Field Study - E. A. Bernays; M. S. Singer; D. Rodrigues (Journal of Insect Behavior, 2004)

Changes in taste receptor cell sensitivity in a polyphagous caterpillar reflect carbohydrate but not protein imbalance - R. F. Chapman; M. S. Singer; E. A. Bernays (Journal of Comparative Physiology A, 2004)

Experience influences gustatory responsiveness to pyrrolizidine alkaloids in the polyphagous caterpillar, Estigmene acrea - R. F. Chapman; E. A. Bernays; M. S. Singer; T. Hartmann (Journal of Comparative Physiology A, 2003)

Topotecan in the Treatment of Acquired Immunodeficiency Syndrome-Related Progressive Multifocal Leukoencephalopathy - W Royal III; B Dupont; D McGuire; L Chang; K Goodkin; T Ernst; MJ Post; D Fish; G Pailloux; H Poncelet; M Concha; L Apuzzo; et al. (Journal of NeuroVirology, 2003)

Hemifacial microsomia: progress in understanding the genetic basis of a complex malformation syndrome - D. Kelberman; J. Tyson; D. Chandler; A. McInerney; J. Slee; D. Albert; A. Aymat; M. Botma; M. Calvert; J. Goldblatt; E. Haan; N. Laing; et al. (Human Genetics, 2001)

High gene flow levels lead to gamete wastage in a desert spider system - Susan E. Riechert; Frederick D. Singer; Thomas C. Jones (Genetica, 2001)

Sensitivity to chemically diverse phagostimulants in a single gustatory neuron of a polyphagous caterpillar - E. A. Bernays; R. F. Chapman; M. S. Singer (Journal of Comparative Physiology A, 2000)

Frequency of partial and missing rings in Acer saccharum in relation to canopy position and growth rate - Craig G. Lorimer; Sally E. Dahir; Matthew T. Singer (Plant Ecology, 1999)

Population subdivision among desert bighorn sheep ( Ovis canadensis ) ewes revealed by mitochondrial DNA analysis - W. M. Boyce; R. R. Ramey; T. C. Rodwell; E. S. Rubin; R. S. Singer (Molecular Ecology, 1999)
We used behavioural observations and mitochondrial DNA (mtDNA) sequence analysis to examine demographic and genetic structure within and among home‐range groups of desert bighorn sheep ( Ovis canadensis ) ewes in the Peninsular Ranges of southern California, USA. We identified substantial genetic variation in the first 515 bp of the mtDNA control region and determined that seven haplotypes were distributed in a nonrandom fashion among these ewe subpopulations. Although a significant ( P

Growth, cold-hardiness, protein content, and digestibility of 70 Leucaena seedlots on three sites in Texas, USA - P. Felker; C.T. Sorensson; D. Ueckert; P. Jacoby; E. Singer; R. Ohm (Agroforestry Systems, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of Presentations at the 19th Congress of the Israeli Phytopathological Society - M. Raviv; I. Nir; Y. Pinkas; E. Shabi; S. Elisha; Marcell Maimon; Y. Szmulewich; S. Freeman; E. Shabi; Y. Nitzani; Talma Katan; Y. Luzzati; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

A9 Fibroblasts Transfected with the m3 Muscarinic Receptor Clone Express a Ca2+ Channel Activated by Carbachol, GTP and GDP - D. Singer-Lahat; E. Rojas; C.C. Felder (The Journal of Membrane Biology, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

HIV-gp120 induced cell death in hematopoietic progenitor CD34+ cells - N. K. Banda; J. A. Tomczak; E. J. Shpall; J. Sipple; R. K. Akkina; K. S. Steimer; L. Hami; T. J. Curiel; G. Singer Harrison (Apoptosis, 1997)

Mating system and mating success of the desert spider Agelenopsis aperta - F. Singer; Susan E. Riechert (Behavioral Ecology and Sociobiology, 1995)

Mating system and mating success of the desert spider Agelenopsis aperta - Fred Singer; Susan E. Riechert (Behavioral Ecology and Sociobiology, 1995)

Definition of human papillomavirus type 16 DNA levels in low and high grade cervical lesions by a simple polymerase chain reaction technique - G. Terry; L. Ho; D. Jenkins; M. Hills; A. Singer; B. Mansell; E. Beverley (Archives of Virology, 1993)